Improving Cognitive Learning Outcomes in Mathematical Problem Solving Through the Problem-Based Learning (PBL) Model for Grade 3 Students at SDN Baddurih - Nur Indah Putri Ayu Pratama Roda'i; Agung Setyawan; Willy Nofriza Putra (Journal of Action Research in Education, 2025)
This study aims to improve cognitive learning outcomes in mathematics problem-solving through the implementation of the Problem-Based Learning (PBL) model for third-grade students at SDN Baddurih. This research is a Classroom Action Research (CAR) conducted in two cycles. The subjects of the study are 14 third-grade students at SDN Baddurih. Data collection techniques include tests, observations, and documentation. The research instruments consist of cognitive learning outcome tests, interview guidelines, and documentation. The data analysis technique used is descriptive analysis. The results of the study show that the implementation of the PBL learning model has been proven effective in improving cognitive learning outcomes in mathematics problem-solving. In Cycle 1, using the conventional method, the percentage of students achieving learning mastery was only 50%. However, in Cycle 2, after applying the PBL model, the percentage of students achieving learning mastery increased to 78.57%, with the class average score rising from 62.14 to 76.43. Learning through PBL actively engaged students in solving mathematics problems, significantly improving their understanding of the material. In conclusion, the application of the PBL model has proven effective in improving cognitive learning outcomes in mathematics problem-solving for third-grade students at SDN Baddurih. It is recommended that teachers apply the PBL model, schools support its implementation, and future researchers further develop more comprehensive studies.